Rogai por nós agora e na hora da nossa morte: o discurso religioso e as injustiças da sociedade na prédicas "Dores de Maria" de Antônio Conselheiro - Andrade, Izaias Geraldo de (2008)
A mentality of indifference to inequality, violence and exclusion is common in our country. It seems as if the presence of opulence and wealth of the few was natural. A culture of acceptance of such situations exists, and it believes that it is possible to conciliate democratic ideals and liberties and with a thoroughly unjust a social structure. Our study focalizes on the Sermons, Pains of Maria which constitute the first part of the manuscript of Antônio Conselheiro, published by Ataliba Nogueira. We conclude that the movement of Canudos had religiosity as the driving force and was led by a man of great religious motivation. He received an ambiguous tradition but revived the potentialities in it. In this way our study seeks to value the religious experience which is reflected in the preaching and career of the leader /beato as a reply to the historical and social context. It is well known that the life of Antônio Conselheiro in Canudos was much more concerned for social justice than scholars have assumed. Antônio Conselheiro was not an insane person, fanatic, beato or any another derogatory name given to him. He was an intelligent leader. The methodology of our study is an analysis of the sermons. Such an analysis helped us to interpret the social injustice then existing in Canudos